Respostas fisiológicas e bioquímicas de Rhizophora mangle L. e Laguncularia racemosa Gaerth. à população ambiental no manguezal do município de Vitória, ES - Falqueto, Antelmo Ralph (2005)
This research was done in order to evaluate the effects of environmental alterations on photosynthesis in Rhizophora mangleL. and Laguncularia racemosaGaerth. young plants. The data were collected during the rain and drought periods in four points atmangrove ofVitoria, ES. The obtained results indicated that the increase in absorption of iron and zinc for L. racemosaduring the dry period favored the reduction of initial fluorescence (Fo). Decreases Foindicate protection of photosynthetic machinery against damage generate by excess of energy excitation, which reflex immediately in the increase to photosystem II photochemical efficiency (PSII), Fv/Fm, in L. racemosa in dry period. The elevated values of Fv/Fmratio observed in thepointnumber 2during the rain period, in both species, constitute good indicators in thenitrogen concentration, which reflex the degree of contamination by pollution threw awaydirectly in the mangrove ecosystem. In the points of higher environmental pollution, has been observed higher use efficiency of ATP and NADPH (Ft) produced during the photochemical phase of photosynthesis, increasedof the Calvin cycle reactions velocity (Fm/Ft) and the CO2fixation ratio (Tdf) in R. mangle and L. racemosa, indicating increase to tolerance thesespecies to environment variations through to increase of photosynthetic rate